Analisis Dampak Penggunaan TikTok terhadap Minat Belajar Siswa - Marliana, Anisa; Rokayah, Siti; Farhurohman, Oman (FONDATIA, 2024)
The aim of this research is to investigate the impact of the use of the TikTok application on the learning behavior of elementary school students. The research method used is a qualitative descriptive method, where data is collected through structured interviews with fellow female students who have experience as teachers in several Islamic Ibtidaiyah Madrasas (MI) and Private Ibtidaiyah Madrasas (MIS). The use of TikTok can influence changes in behavior in children, both moral and social behavior in their environment. So careful, continuous supervision and restrictions by teachers and parents are needed regarding children's use of TikTok. Based on the results of research from several researchers, it is stated that TikTok has a relevant influence on students' interest in learning, to the point that it becomes a concern for teachers, namely that it also influences learning outcomes.